PENGARUH PENDIDIKAN KESEHATAN TERHADAP TINGKAT PENGETAHUAN TENTANG PEMERIKSAAN PAYUDARA SENDIRI (SADARI) PADA REMAJA PUTRI DI DUSUN KERET DESA SUMBERJATI, MOJOANYAR MOJOKERTO - Mardiyana, Rina; Tri Handayani, Desi (JURNAL KEPERAWATAN BINA SEHAT, 2015)
SADARI or breast self-examining is the easiest, the cheapest and the simplest way to detect breast cancer earlier. Many people don’t know yet about this earlier detection activity. The aim of this research is to find out the influence of the health education about breast self-examining (SADARI) toward the level of girls’ knowledge in Keret village. The design which is used in this research is pre-experimental with pre-post test type in a group (one group pra-post test design). There are some variables that are used in this research, free variable that is used is health education about breast self-examining (SADARI), while the tied variable is the level of girls knowledge in Keret village. The population is Keret village girls about 41 respondents. Data taken using a questionnaire. Data were analyzed using descriptive analysis. The result was no defference in getting the level of knowledge of girls in keret village before and after health education about knowing that the average before being given health education after 4,88 becomes 9,95 that given health education. From this result, girl’s are expected to continuouslylearn to improve awareness and increase knowledge and skills in doing breast self examining (SADARI), especially the stages to do brest self examining (SADARI) so that the earlier the breast cancer is known the higher the number of healing.Keywords:SADARI, health education, knowledge.